Gall bladder cancer: A single center experience - Rawal, Sushil Bahadur; Shah, Kunda Bikram; Shrestha, Dhana Bahadur; Malla, Srijan; Rayamajhi, Jyoti; Jha, Manoj Kumar; Thapa, Anup (Birat Journal of Health Sciences, 2018)
Introduction Gallbladder cancer (GBC) is the most common malignancy of the biliary tract, which is increasing in Southeast Asia. An early diagnosis is crucial for curative surgical resection. However, patients present late because at an early stage the initial symptoms are non- specific. Radical surgery is a challenging operation, and should be carried out only if R0 resection is feasible. Objectives: The aim of this study was to analyse the patient profile, clinical presentation and peri-operative outcome of patients who underwent various surgeries for GBC. Methodology: Patients who had undergone surgery for GBC at our center over a 7 year period were identified from our database. A retrospective analysis from prospectively collected data was done. We analysed the outcome of these patients over the study period. Results: Forty-four patients underwent surgery for GBC. There was a female preponderance (34 patients; 77%) and the mean age of the patients was 54 years (range 22-76 years). Thirty-six patients (82%) were diagnosed pre-operatively. Extended cholecystectomy (either segment IVb/V or 2cm nonanatomical wedge resection of the liver) with standard lymph node clearance was performed in 35 patients (79%). Peri-operative complications was seen in 11 patients (25%) and in hospital mortality was seen in 2 patients (4.5%) Conclusion: GBC is the most common malignancy of the biliary tract. As majority of patient present with locally advanced disease a potential curative resection warrants an aggressive surgical approach, which includes liver resection, lymph node clearance and resection of involved adjacent organs. Although this is a formidable surgery, it is the only chance for long-term survival. BJHS 2018;3(2)6:427-431.